Prevalence of gestational diabetes mellitus in mainland China: A systematic review and meta‐analysis - Chenghan Gao; Xin Sun; Li Lu; Fangwei Liu; Jing Yuan (Journal of Diabetes Investigation, 2019)
Abstract Aims/Introduction Pregnant women with gestational diabetes mellitus (GDM) are at a higher risk of adverse pregnancy outcomes. The aim of the present study was to estimate the pooled prevalence of GDM in mainland China according to International Association of Diabetes and Pregnancy Study Groups criteria. Materials and Methods We carried out a systematic review by searching both English and Chinese literature databases. Random effects models were used to summarize the prevalence of GDM in mainland China. Subgroup and sensitivity analyses were carried out to address heterogeneity. Publication bias was evaluated using Egger's test. Results A total of 25 papers were included in the meta‐analysis, involving 79,064 Chinese participants. The total incidence of GDM in mainland China was 14.8% (95% confidence interval 12.8–16.7%). Subgroup analysis showed that the age, bodyweight and family history of diabetes mellitus could significantly increase the incidence of GDM. Conclusions To the best of our knowledge, this systematic review is the first to estimate the pooled prevalence of GDM among women in mainland China according to International Association of Diabetes and Pregnancy Study Groups criteria. The results of our systematic review suggest a high prevalence of GDM in mainland China, indicating that this country might have the largest number of GDM patients worldwide.